At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Find the 66th term of the arithmetic sequence -28,-45,-62

Sagot :

Answer:

Using the formula

an = a of 1 + (n-1)(d)

an = -28 + (n-1)(-17)

simplify

an = -17n - 11

Now that we have the formula, we just plug in 66 for n

a66 = -17(66) - 11

a66 = -1133